EKSISTENSI KELUARGA SINGLE PARENT (Analisis Keluarga Single Parent Di Desa Samirono Perspektif Struktural Fungsional) - Fikri, Sariatul; Nur Fitria Primastuti; Nur Sodiq (LPPM STAI Muhammadiyah Probolinggo, 2024)
There is a phenomenon where one parent takes care of their child (single parent). Even though legally the parents are obliged to care for children. So how can the existence of one parent caring for their child (single parent) survive? This research examines the existence of one parent caring for their child using Talcot Parson's AGIL theory. This type of research is field research with qualitative methods. The subject and locus of this research are single parent families in Samirono Village, District. Getasan District. Semarang. Researchers used primary data through in-depth interviews with perpetrators and secondary data obtained from literature. The research results show that the adaptation function can be seen from adaptation with the family or in society, the integration function is in the form of maximum child care from single parents, and the integration function includes good time management between child care and domestic household work. Meanwhile, the function of latency is that there is no intention from single parents to live in a household with a new person because they want to focus on caring for and educating their children. Keyword: Existence, Samirono, Single parent